Comparison of black carbon concentration and particle mass concentration with elemental carbon concentration for multi-walled carbon nanotube emission assessment purpose. (October 2017) - Kim, Won-Geun; Yong, Sang-Don; Yook, Se-Jin; Ji, Jun Ho; Kim, Kyung-Hwan; Bae, Gwi-Nam; Chung, Eun-Kyo; Kim, Jeong Ho
Abstract: Elemental carbon (EC) can cause lung cancer or inflammation. Therefore, the objective of this study is to identify the possibility of real-time estimation of the EC concentration of multi-walled carbon nanotubes (MWCNTs) for workplace emission assessment. MWCNT aerosol particles were generated at a relatively constant rate over a period of 24 h, and the aerosolized MWCNTs were generally smaller than 1 μm. On-line measurement was performed by using an aethalometer and a scanning mobility particle sizer (SMPS) to determine black carbon (BC) concentration and particle mass concentration of the MWCNTs, respectively. Off-line analysis was conducted according to the National Institute for Occupational Safety and Health (NIOSH) method 5040 to obtain EC concentration of the MWCNTs. Then, correlations among the BC concentration, particle mass concentration, and EC concentration were investigated for the MWCNT particles. The particle number concentration converted from the SMPS measurement data and the BC concentration measured by the aethalometer were found to be in linear relation with the filter-sampling-based EC concentration, when the EC concentration of the MWCNTs was determined by the NIOSH method 5040. It is therefore anticipated that the use of the aethalometer and the SMPS can be of great help to the MWCNT emission assessment. Graphical abstract: